O agir do/a revisor/a de textos sob uma perspectiva social e interacionista - Lemos, Mayara Espindola (2019)
The proofreading is a complex activity and it requires skills and abilities which go beyond all types of knowledges and grammar of a language, granting the proofreader professional an important role on society. The goal of this research is the reflection of the proofreader professional under a social and interactional approach, regarding its attitude towards a text. The analysis of this relation was possible by using two instruments: a questionnaire and the texts corrected by proofreaders, once they reveal attitudes and also promote reflection about the profession. The theoretical basis of this study is the Socio-Discursive Interactionism (SDI) framework developed by Jean Paul Bronckart (2006, 2008, 2009) and its notions of work, activity, task and attitude. In this research, the proofreading procedures are also considered in its language and its conditions of production, internal and external to the text, according to the SDI approach. The corpus was analyzed based on four criteria: (1) the particular attitude of the proofreader, (2) the modes of its attitude while working, (3) the internal aspects of a text and (4) the external aspects of a text which are relevant to the proofreader. The data showed that proofreading is not an isolated and individual activity, but socially oriented, which reinforces its role as a profession on high literate societies.